The types of Chilopoda and Diplopoda (Myriapoda) housed at the Museo de La Plata, Argentina - Pereira, Luis A.; Ituarte, Cristián; Tassara, Mónica P. (Zootaxa, 2004)
A complete list of the type specimens of Myriapoda in the collection of the Division of Invertebrate Zoology at the Museo de La Plata, Argentina, is given. A total of 757 type specimens are listed. The types belong to 24 nominal species of Chilopoda Geophilomorpha, 2 nominal species and 3 nominal subspecies of Chilopoda Scolopendromorpha, and 8 nominal species and 2 nominal subspecies of Diplopoda Polydesmida. The authorship of taxa correspond to: B cherl (1); Coscar n (4); Pereira (7); Pereira & Coscar n (2); Pereira & Minelli (3); Pereira, Minelli & Barbieri (7); Pereira, Foddai & Minelli (5) and Schubart (10).